Possibility in impossibility?: working with beginning teachers of English in times of change - McIntyre, Joanna; Jones, Susan (Wiley Online Library, 2014)
Beginning teachers of English are entering a profession in which their subject is increasingly framed according to prescriptive models of literacy. This is happening at a time of shift away from university ITE provision towards schoolled training. We offer a spatialised theorisation of the ways in which beginning teachers of English have drawn from the balance of practical and theoretical approaches encountered in their qualifying year to engage with tensions between policy and practice. We suggest that university ITE provides important interstitial spaces in which they can explore some of these tensions and navigate pedagogies, principles and values. In doing so, they are negotiating alternatives, which, we argue, represent powerful potential for their future within the profession.